Respuesta :
Answer:
r=7
Step-by-step explanation:
8r-13=43
Undo!
8r= 43+13
8r=56
r=56/8
r=7
Answer:
8(7)-13=43
R= 7
Step-by-step explanation:
13 less than 8R leaves 43.
R is the unknown.
This expression can be in an equation.
8R-13= 43
Carry over the like terms. Carry over the -13 and make R the subject.
8R= 43+13
8R= 56
R= 56/8
R= 7
To check if the answer was correct, replace the unknown which is R with the value of what it is in brackets. Remember brackets mean to multiply.
8(7)-13= 43
56-13= 43
Therefore the answer is 7